Root decomposition and nutrient dynamics in multifunctional forage‐biomass buffer‐strip systems - Helen C. S. Amorim; Amanda J. Ashworth; Taylor C. Adams; Mary C. Savin; Philip A. Moore Jr. (Agrosystems, Geosciences & Environment)
Abstract Perennial crops are thought as a solution for enhancing food security and providing ecosystem services under a changing climate, including forage‐biomass production, reduced erosion and nutrient leaching, and soil C accumulation. However, the drivers of root decomposition and C allocation in perennial multifunctional forage‐biomass buffer‐strips as affected by fertility management are poorly elucidated. Thus, study objectives were to assess root decomposition and soil CO2 efflux on switchgrass (Panicum virgatum L.), eastern gamagrass (Tripsacum dactyloides L.), silphium (Silphium integrifolium Michx.), and intermediate wheatgrass Kernza (Thinopyrum intermedium [Host] Barkworth & D.R. Dewey) treated with poultry litter (PL) relative to the unfertilized control. Root mass loss was greatest for silphium, owing to low neutral and acid detergent fibers and lignin contents (6%) relative to the other species (16%–25%). Root‐C loss was the greatest for intermediate wheatgrass (IW), mostly driven by hemicellulose degradation. Low root mass, surface area, and volume likely enhanced root decomposition for silphium and IW. Root mass loss and C, N, and P mineralization for novel perennial buffer‐strip species were greater in PL plots. Soil organic C stocks were mostly similar across forage‐biomass species × amendment combinations. Silphium‐PL had 27%–50% greater SOC stocks after 4 years, owing to higher root sloughing and C inputs to soil. Root decomposition rates were primarily affected by root chemical composition and morphology, while soil CO2 efflux was driven by soil moisture and temperature. Greater root sloughing, C inputs, and nutrient cycling showcase the potential for C storage and multiple purposes of novel perennial buffer‐strips.